Pengembangan Game Literasi Numerasi berbasis RPG Maker MV - Eldiana, Novia Frisda; Zainuddin, Muhammad; Arifin, Slamet (Universitas Nahdlatul Ulama Blitar, 2025)
This research aims to develop numeracy literacy games based on RPG Maker MV in the form of games that are declared valid and games that are declared practical. The method used in this research is development research with a prototyping model according to Nieveen which has stages; 1) preliminary research, 2) prototyping stage, and 3) assessment stage. The instruments used were interview sheets and questionnaire sheets. The interview sheet was used to explore information about the needs of the school, while the questionnaire sheet was used to validate and respond to the practicality of the game. The validity of the game was determined from the results of validation by mathematics expert lecturers and teachers. Practicality is obtained from filling out a response questionnaire from using the game by students and teachers. The test subjects were elementary school students in Durenan sub-district, especially grade V students. Limited trials were conducted on 7 students and field trials were conducted on 21 students. The resulting device can be said to be good if it meets the criteria of valid and practical. The results of game validation are 85.7 from media experts. The results of validation from material experts consisted of 91.6 from lecturers and 88.9 from teachers. The results of the student response practicality questionnaire were 90.6 and the teacher response practicality questionnaire was 92.6. So, the conclusion is that the numeracy literacy game based on RPG Maker MV is valid and practical to use in the learning process.